NEW YORK'S STATE LEGISLATURE SET TO RAISE EXCISE TAXES. POSSIBLY AS EARLY AS TODAY. (Tufts Archival Research Center, 2007)
Document opposing Governor Pataki's hike in the cigarette tax. Explains that the tax is earmarked for increases in the salaries of New York State workers and is an addition to the tax levied two years prior which was earmarked for health care costs. Asks people to oppose the tax by writing to the governor.